2015
DOI: 10.1039/c5sm01580d
|View full text |Cite
|
Sign up to set email alerts
|

Dimensional reduction of duplex DNA under confinement to nanofluidic slits

Abstract: There has been much interest in the dimensional properties of double-stranded DNA (dsDNA) confined to nanoscale environments as a problem of fundamental importance in both biological and technological fields. This has led to a series of measurements by fluorescence microscopy of single dsDNA molecules under confinement to nanofluidic slits. Despite the efforts expended on such experiments and the corresponding theory and simulations of confined polymers, a consistent description of changes of the radius of gyr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
18
1

Year Published

2015
2015
2024
2024

Publication Types

Select...
10

Relationship

4
6

Authors

Journals

citations
Cited by 17 publications
(21 citation statements)
references
References 64 publications
2
18
1
Order By: Relevance
“…This conclusion should not be extended to DNA under high confinement (scales on the order of the persistence length a) since the strength of the excluded volume interaction should be greatly amplified under these conditions. 51 Our conclusions also do not apply to low salt conditions where long-range electrostatic interactions must have an appreciable effect on the dimensions of DNA.…”
Section: Discussionmentioning
confidence: 56%
“…This conclusion should not be extended to DNA under high confinement (scales on the order of the persistence length a) since the strength of the excluded volume interaction should be greatly amplified under these conditions. 51 Our conclusions also do not apply to low salt conditions where long-range electrostatic interactions must have an appreciable effect on the dimensions of DNA.…”
Section: Discussionmentioning
confidence: 56%
“…For instance, ν eff is a function of the aspect ratio r for oblate and prolate ellipsoids, where r is the ratio between the largest to the smallest ellipsoid axis. 24 The same situation arises for dendrimers, 25,26 duplex DNA, 27 carbon nanotube domains, 8 nanoparticle with grafted layers of DNA chains, 28,29 etc. In each case, the molecular parameters describing the object must be prescribed over which the mass scaling relation is exhibited.…”
Section: Scaling Relationship Between α E C and R Gmentioning
confidence: 87%
“…We found that the free energy converges more quickly than the chain size, which is convenient for our purposes. The predictions by de Gennes for both of the in-plane radius of gyration [17, 19, 28, 30, 31, 40, 42, 43, 46] and confinement free energy [29, 30], or equivalently the force of the confinement [31, 42], have been verified many times. There is one report [39] claiming that the de Gennes theory for the confinement free energy fails for long chains; our results correspond to very long chains simulated with a state-of-the-art methodology and the agreement of the data in Fig.…”
Section: Simulation Methodsmentioning
confidence: 99%